2023
DOI: 10.1055/s-0043-1771009
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Pediatric Foreign Body Ingestions and Food Bolus Impactions: A Retrospective Study from a Tertiary Care Center

Abstract: Background Foreign body (FB) ingestion is a common pediatric problem with the majority of these occurring in children younger than 3 years. Management varies depending on the age of the patient, ingested object(s), its location along the digestive tract, and the available expertise. We aim to report our experience with endoscopic management of FB ingestions in children (<18 years). Materials and Methods We retrospectively reviewed and analyzed endoscopic and medical records from our hospital datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…11 Another retrospective study from a tertiary care center reported a large number of children undergoing successful endoscopic retrieval of ingested foreign bodies. 12 The journal also published a number of endoscopy images last year. Sharma et.…”
mentioning
confidence: 99%
“…11 Another retrospective study from a tertiary care center reported a large number of children undergoing successful endoscopic retrieval of ingested foreign bodies. 12 The journal also published a number of endoscopy images last year. Sharma et.…”
mentioning
confidence: 99%